Pengaruh FDR, NPF, CAR, dan BOPO Terhadap Profitabilitas Bank Umum Syariah di Indonesia - Chavia Gilrandy La Difa; Diharpi Herli Setyowati; Ruhadi Ruhadi (Journal of Applied Islamic Economics and Finance, 2022)
This research aims to analyze the impact of several financial ratios, namely (FDR), (NPF), (CAR) and (OER), on the profitability of Indonesian Islamic Commercial Banks from 2015 to 2019. The sample size is 12 BUS, and the time period is 2015-2019 (5 years). Using Panel Data Regression Analysis Method According to the research, the selected estimate is the Randon Effect Model (REM). The hypothetical results show that the variables NPF, FDR, CAR and BOPO have a significant effect on ROA at the same time, with a significance value of 0.00000. Part of the test results show that FDR variables do not affect ROA, while NPF, CAR, and BOPO variables have significant effects on ROA. The determinant coefficient of Adjusted R2 is 0.792175 or 79,2175%, which means that the four independent variables can explain the dependent variable, while the rest are affected by other factors.